Analysis of Knowledge towards Mother's Behavior in Choosing Food Menus to Support Toddler Fitness in the Covid-19 Pandemic - Paramitha, Intan Azkia; Saputri, Herliyani Dwi; Puspa, Mutiara (Prosiding University Research Colloquium, 2022)
Indonesia is in the top five for cases of malnutrition. Nationally, it is estimated that around 4.5% of 22,000,000 children under five or 900,000 children under five are malnourished or malnourished. This study aims to analyze the relationship between knowledge and the behavior of mothers in choosing food menus to support the fitness of children under five in the Covid-19 Pandemic, especially in Pekalongan Regency. This research is a quantitative descriptive study exploring the behavior of mothers who have toddlers with cross sectional method. Sample technique using purposive sampling. The sampel size in this study was 107 mothers who had children from 0 months to 5 years of age. The results of the Pearson Chi-Square statistical test obtained P-Value 0.000, namely there is a significant relationship between mother's knowledge and mother's behavior in choosing food menus in Pekalongan Regency. Therefore, the role of health workers in providing accurate and fast information during a pandemic is very meaningful in increasing the knowledge of mothers who have toddlers.